Castro, leading economists to speak at agribusiness conference - Hughes, Eddie::::::::: (2013)
Top economists will join academic and business experts to discuss the economic outlook, global trade agreements, California's water supply, immigration policy reform and other issues at the 32nd Annual Agribusiness Management Conference.